Why should I switch on my camera? Developing the cognitive skills of compassionate communications for online group/teamwork management - Jayasundara, J. M. P. V. K.; Gilbert, Theo; Kersten, Saskia; Meng, Li (Frontiers in Psychology, 2023)
Introduction Associated with learning and social isolation from each other during the pandemic-driven transition to online platforms in Higher Education (HE), many students were, and remain, reluctant to turn on their video cameras to be present with each other during their online meetings. Using the Compassionate Mind Foundation's definition of compassion, not as an emotion, but as a psychobiological motivation to take wise action to help when self or others struggle, this comparative study examined (a) the deployment by students during online, task-focused group/team meetings, of taught verbal and non-verbal communication strategies that were explicitly compassionate and (b) the effects of these strategies on each other's social and learning experiences in these meetings, compared to when they did not use them. Methods Twenty-four STEM students from a sample of five Sri Lankan universities, were mixed, then divided into six groups of four students per group. This mixed-methods study, video-recorded and analyzed each group's task-focused group meetings before, then after, an online interactive 90-min training session (the intervention) in the Cognitive Skills of Compassionate Communications (CSCC) for groups/teams. Results Using R, SPSS and Microsoft Excel to analyse the quantitative data, a statistically significant improvement in students' screen-gaze attentiveness was identified after the CSCC intervention. The qualitative data analysis explained this and other behavioral changes that were shown to enhance students' social and learning experiences in their online meetings. Given the strong historical and political drivers of current divisions across Sri Lankan student communities, these findings call for more urgent research on compassion as a cognitive competence for accelerating group/team cohesion and criticality across HE, and beyond.